TEACHER’S STRATEGIES IN TEACHING READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT - Dessy Irene Lasnirohana Sianturi; Nora Ronita Dewi (Universitas Negeri Medan, 2022)
This study investigated teacher’s strategies in teaching reading comprehension of analyticalexposition text. This study was conducted by using descriptive qualitative method. Therespondents of this research were one English teacher and nineteen students of XI IPS 2 class inSMA Negeri 1 Bangun Purba. The instrument for collecting the data was a video recorder andquestionnaire dissemination. The teacher was observed and recorded when applied teachingstrategies in reading comprehension of analytical exposition text. Meanwhile, the students had tofill the questionnaire to state their problems towards the teacher’s strategies in teaching readingcomprehension of analytical exposition text. The result indicated that the teacher implied generalmethods such as introducing text, setting the reading purpose, skimming the text, translating thetext, answering question and identifying answer. Meanwhile, the most difficult strategyaccording to the students was skimming text. There were 11 of 19 students who stated thatskimming text was difficult since they did not possess good vocabulary mastery. The leastdifficult strategy was identifying answer. Based on the data, teacher might need to improve thestrategies to overcome students’ problems in reading comprehension of analytical exposition text